UTM Degree++ Program Area: Safety & Health At Work - Kidam, Kamarizan (2007)
The responsibility for a safe and healthful workplace does not merely lie in the hands of company management. According to OSHA 1994, all employees are equally responsible for ensuring the workplace is safe and should received adequate training to safely execute their duties. Each employee, especially a new comer, must be advised with basic lesson of safety and any hazards related to their specific task or activities.